Etnomathematic Exploration At Tjoe Tik Kiong Pasuruan Temple - Istiqomah (Jurnal QOSIM : Jurnal Pendidikan, Sosial & Humaniora, 2025)
The mathematical concepts that appear in the Tjoe Tik Kiong monastery building are geometry, congruence, congruence, and geometric transformation. The purpose of this research is to find out what is ethnomathematics in Tjoe Tik Kiong Pasuruan Monastery. This type of research is qualitative research with an ethnographic approach. The subjects of this research are one religious figure and one craftsman. The data collection techniques used are observation and interview. The results of this study reveal that there are several ethnomathematics in the Tjoe Tik Kiong Temple. The ethnomathematics obtained at the temple consists of the concepts of flat buildings, space buildings, geometric transformations, congruence, and perpendicularity. The ethnomathematics resulting from this research can then be used for student teaching materials. This teaching material contains questions, discussions, and guides to find out student difficulties. The material of the teaching materials is about the concept of flat buildings, regular hexagon prisms, and geometric transformations. Based on the results of the study, researchers hope to develop teaching materials that are interesting and at the same time introduce various temple buildings in Pasuruan. By utilizing ethnomathematics, it can help teach mathematics from a cultural point of view and be a breakthrough to teach mathematics learning material so that it is not boring.